Pretreatment of biomass using ionic liquids: Research updates. (October 2017) - Zhang, Quanguo; Hu, Jianjun; Lee, Duu-Jong
Abstract: Room-temperature ionic liquids (ILs) are molten salts at around room temperatures. The current researches of using ILs for efficient pretreatment for lignocellulosic biomass are updated in this article. The aspects of synthesis of high-performance ILs, recycling of used ILs with minimum use of utility, development of IL-tolerant enzymes, and optimization of the entire process economy were discussed. The mechanisms of IL solvation and the potential for IL-based biomass refinery are also highlighted.